(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
India is blessed with a great number of good talented flourishing cartoonists with political awareness, sense of satire and original draftsmanship. They typically combine artistic skill, hyperbole and satire in order to question authority and draw attention to corruption, political violence and other social ills. A good political cartoon makes you think about current events, but it also tries to sway your opinion toward the cartoonist’s point of view. The best political cartoonist can change your mind on an issue without you even realizing how he or she did it.Unlike many countries, India is a place where for generations politicians actively enjoyed seeing themselves in cartoons. However, thirst for political cartoons among newspaper readers with different languages has increased very much. There is hardly a paper today, which does not carry a cartoon, whether it is good, bad or indifferent. Just to satisfy the reader’s expectation and habit, sometimes embarrassingly poor efforts get into the columns of the paper.The paper will begin with the assumption of the importance of political cartoons in the newspapers now days. A detail study in this context shows an overview about political cartoons as a means of print media communication and the contribution of art of political cartoons by great cartoonist of India.